Synthetic biology for medical biomaterials - Tao Xu; Xiao‐Yun Huang; Jin‐Wei Dao; Da Xiao; Dai‐Xu Wei (Interdisciplinary Medicine, 2025)
Abstract After more than 20 years of development, synthetic biology has emerged as an interdisciplinary field that integrates biology, medicine, mathematics, and engineering. By constructing and regulating genetic elements, networks, and pathways, artificially engineered bacteria, cells, or viruses can directly interact with the human body to enable disease treatment via synthetic biology. Additionally, synthetic biology platforms have been employed in the production of medical biomaterials (MBMs), indirectly contributing to the maintenance of human health. In this review, we present a range of typical MBMs derived from synthetic biology platforms, including polylactic acid, polyhydroxyalkanoates, hyaluronic acid, collagen, poly(β‐hydroxybutyrate), poly(β‐malic acid), poly‐γ‐glutamic acid, alginate, chitosan, bacterial cellulose, and antimicrobial peptides. We also introduce the key synthetic biology techniques and tools involved, such as chassis cell design, gene expression regulation and editing tools represented by CRISPRi, metabolic engineering, cell morphology engineering, and cell‐free systems. Furthermore, we summarize recent advancements and strategies including enhancing production and cost‐reduction, biosynthesis of novel materials, regulating material characteristics and diversity, minimizing toxicity in biosynthetic systems, and designing engineered living materials in the research applications and clinical translation of synthetic biology for MBMs. Finally, we discuss emerging trends that may shape the future biomedical applications of synthetic biology.